Stress-Strain Relation and Nonlinear Behavior of Circular Confined Reinforced Concrete Columns - Tavio, Tavio; Tata, Arbain (Department of Civil Engineering, Diponegoro University, 2008)
This paper presents a nonlinear finite element modeling and analysis of circular normal-strength reinforced concrete columns confined with transverse steel under axial compressive loading. In this study, the columns were modeled as discrete elements using ANSYS nonlinear finite element software. Concrete was modeled with 8-noded SOLID65 elements that can translate either in the x-, y-, or z-axis directions from ANSYS element library. Longitudinal and transverse steels were modeled as discrete elements using 3D-LINK8 bar elements available in the ANSYS element library. The nonlinear constitutive law of each material was also implemented in the model. The results indicate that the stress-strain relationships obtained from the analytical model using ANSYS are in good agreement with the experimental data. This has been confirmed with the insignificant difference between the analytical and experimental, i.e. 1.011 and 1.306 percent for the peak stress and the strain at the peak stress, respectively. The comparison shows that the ANSYS nonlinear finite element program is capable of modeling and predicting the actual nonlinear behavior of confined concrete column under axial loading. The actual stress-strain relationship, the strength gain and ductility improvement have also been confirmed to be satisfactorily. Keywords: ANSYS, confinement, ductility, stress-strain relationship, nonlinear finite element analysis, nonlinear behavior, reinforced concrete columns, strength ABSTRAK Makalah ini menyajikan pemodelan dan analisis elemen hingga nonlinier kolom bulat beton normal bertulang yang dikekang dengan baja transversal dibawah pembebanan aksial tekan. Dalam studi ini, kolom dimodelkan sebagai elemen diskrit menggunakan perangkat lunak elemen hingga nonlinier ANSYS. Beton dimodelkan dengan elemen SOLID65 8-titik yang dapat bertranslasi baik dalam arah sumbu-x-, -y, or -z dari pustaka elemen ANSYS. Baja longitudinal dan transversal dimodelkan sebagai elemen diskrit menggunakan elemen batang LINK8-3D yang tersedia dalam pustaka elemen ANSYS. Hukum konstitutif nonlinier setiap material juga diterapkan dalam model. Hasilnya menunjukkan bahwa hubungan tegangan-regangan yang diperoleh dari model analisis menggunakan ANSYS sangat sesuai dengan data eksperimental. Hal ini telah dikonfirmasi dengan perbedaan yang tidak signifikan antara hasil analisis dan eksperimental, yaitu 1,011 and 1,306 persen masing-masing untuk tegangan puncak dan regangan saat tegangan puncak. Perbandingan menunjukkan bahwa program elemen hingga nonlinier ANSYS mampu memodelkan dan memprediksi perilaku nonlinier aktual kolom beton terkekang dibawah pembebanan aksial. Hubungan tegangan-regangan aktual, peningkatan kekuatan dan perbaikan daktilitas juga telah dikonfirmasi memuaskan.Kata kunci: Analisis elemen hingga nonlinier, ANSYS, daktilitas, hubungan tegangan-regangan, kekuatan kolom beton bertulang, pengekangan, perilaku nonlinierPermalink: http://ejournal.undip.ac.id/index.php/mkts/article/view/3699[How to cite: Tavio dan Tata, A. (2008), Stress-Strain Relation and Nonlinear Behavior of Circular Confined Reinforced Concrete Columns, Jurnal Media Komunikasi Teknik Sipil, Tahun 16, Nomor 3, pp. 255-268]